FTO gene–lifestyle interactions on serum adiponectin concentrations and central obesity in a Turkish population. (3rd April 2021) - Isgin-Atici, Kubra; Alsulami, Sooad; Turan-Demirci, Busra; Surendran, Shelini; Sendur, Suleyman Nahit; Lay, Incilay; Karabulut, Erdem; Ellahi, Basma; Lovegrove, Julie A.; Alikasifoglu, Mehmet; Erbas, Tomris; Vimaleswaran, Karani Santhanakrishnan; et al.
Abstract: The aim of the study was to investigate whether lifestyle factors modify the association between fat mass and obesity-associated (FTO) gene single nucleotide polymorphisms (SNPs) and obesity in a Turkish population. The study included 400 unrelated individuals, aged 24-50 years recruited in a hospital setting. Dietary intake and physical activity were assessed using 24-hour dietary recall and self-report questionnaire, respectively. A genetic risk score (GRS) was developed using FTO SNPs, rs9939609 and rs10163409. Body mass index and fat mass index were significantly associated with FTO SNP rs9939609 ( p  = 0.001 and p  = 0.002, respectively) and GRS ( p  = 0.002 and p  = 0.003, respectively). The interactions between SNP rs9939609 and physical activity on adiponectin concentrations, and SNP rs10163409 and dietary protein intake on increased waist circumference were statistically significant ( P interaction  = 0.027 and P interaction  = 0.044, respectively). Our study has demonstrated that the association between FTO SNPs and central obesity might be modified by lifestyle factors in this Turkish population.